Unveiling hydrosocial dynamics: discourse and power in Peña Blanca - Di Tullio, Viola; Zannini, Lorenzo (Frontiers in Environmental Science, 2025)
Water is not just a material element but a socio-natural object of knowledge whose conceptualisation, policing and management carry symbolic and material implications. This issue becomes especially evident in territories where water scarcity and drought pose heightened social and environmental challenges, not least in the face of climate change. Against this background, our research looks at the long history of water privatisation in Chile and at how it has profoundly impacted water scarcity issues, exacerbated desertification, and led to water conflicts. In particular, in Peña Blanca, an agricultural community in northern Chile, these dimensions intertwine and shed light on the territory’s hydrosocial components. Water and fog tell histories of social dynamics, conflicts, cooperation, and climate change. Taking a discoursive approach to ethnographic fieldwork, the paper will analyse interviews carried out with local actors against the background of on-site observation to explore the discursive construction of water and its sociopolitical consequences in Peña Blanca. The paper aims to provide an original perspective on the symbolic and material implications of hydrosocial identities in climate-exposed communities struggling for autonomy, agency, and self-determination.